Analysis of Community Digital Literacy Levels in the Use of Mobile Banking at Islamic Banks - Ramadhan Asmara, Rizky; Dewi , Hasna; Edi Saputra, Ahmad; Kartika Devi, Erwina; Haeran (Journal of Economics and Social Sciences (JESS), 2025)
This study explores the level of knowledge and understanding of mobile banking services offered by Bank Syariah Indonesia among the community of Kelurahan Mendahara Ilir. Utilizing a qualitative descriptive approach, data were collected through interviews, observations, and document reviews to analyze community experiences and perceptions. Findings reveal that knowledge about mobile banking varies significantly, with younger and more educated individuals demonstrating greater awareness and usage. Major barriers include insufficient socialization and training, unstable internet connectivity, limited data availability, and concerns over digital transaction security. These challenges contribute to the continued reliance on conventional banking methods among certain groups. The study highlights the necessity for intensified and inclusive educational programs, improved digital infrastructure, and user-friendly guidance to enhance digital literacy. Addressing these issues will facilitate broader adoption of mobile banking services and support the advancement of sharia-compliant financial inclusion in the digital age